MicroRNA-221 Modulates Airway Remodeling via the PI3K/AKT Pathway in OVA-Induced Chronic Murine Asthma - Pan, Jing; Yang, Qianyuan; Zhou, Yao; Deng, Huan; Zhu, Yifan; Zhao, Deyu; Liu, Feng (Frontiers in Cell and Developmental Biology, 2020)
Background Airway remodeling is one of the most important pathological features of chronic asthma. This study aimed to determine whether microRNA-221 (hereafter, miR-221) can affect airway remodeling in a mouse model of ovalbumin (OVA)-induced chronic asthma. Methods Adeno-associated viruses (AAVs) “Bearing miR-221 sponges” were used to downregulate miR-221 in asthmatic mice. Staining with hematoxylin and eosin (H&E), Masson trichrome, and periodic acid–Schiff reagent was used to assess histological changes. The affected signaling pathway in mouse airway smooth muscle cells (ASMCs) was also identified by gene chip technology. A PI3K/AKT-inhibitor (LY294002) was used to confirm the role of the pathway in ASMCs. Results The inhibition of miR-221 in a murine asthma model was found to reduce airway hyper-responsiveness, mucus metaplasia, airway inflammation, and airway remodeling (p < 0.05). Furthermore, miR-221 was found to regulate collagen deposition in the extracellular matrix (ECM) of ASMCs. Bioinformatics analysis and western blot analysis confirmed that the PI3K-AKT pathway was involved in ECM deposition in ASMCs. Conclusion miR-221 might play a crucial role in the mechanism of remodeling via the PI3K/AKT pathway in chronic asthma and it could be considered as a potential target for developing therapeutic strategies.